Cognitive evolution of Alzheimer's disease patients according to the serverity of obstructive sleep apnea: Biomarkers (non‐neuroimaging) / Longitudinal change over time. (7th December 2020) - Carnes, Anna; Piñol, Gerard; Dakterzada, Faride; Targa, Adriano; Benitez, Ivan David; Huerto, Raquel; Barbe, Ferran
Abstract: Background: To investigate the effect of OSA on the cognitive evolution of patients with AD. Method: In this prospective, single‐center study (NCT02814045), patients with mild‐moderate AD with and without untreated OSA were evaluated at the baseline and after 12, 24 and 36 months of follow‐up. OSA was defined as an apnea‐hypopnea index (AHI) >15/h. The primary outcome was measured by the cognitive scores on the Alzheimer's Disease Assessment Scale‐Cognitive subscale (ADAS‐cog) and Mini‐Mental State Examination (MMSE). Result: The cohort included 146 patients with 125 validated PSGs, from which 40 patients were diagnosed as non‐OSA (32%) and 85 as OSA (68%). The median [IQR] age of the eligible individuals was 75.0 [72.0;80.0] years and the majority was composed of women (57.25%). In addition, the mean (SD) MMSE score at the baseline was 23.53 (2.23). In the ADAS‐cog score, the mean (SD) change at the 12 months of follow‐up was 2.97 (5.73) and 0.29 (5.65) for the non‐OSA and OSA group, respectively. The estimated mean (95%) difference between the groups was ‐2.76 (0.12 to 0.16) (p=0.033). No cognitive changes were observed at several cognitive domains evaluated. There was a cognitive decline along the 3 years of follow‐up according to the MMSE score (p<0.001) (Figure 1), but no differences between the groups were observed. Conclusion: OSA was not associated with a worse cognitive evolution after 36 months of follow‐up. Further studies will be necessary to improve the understanding of the OSA impact on the cognitive evolution of AD patients.